The cicadas (Hemiptera: Cicadidae) of Panama including the description of six new species, three new combinations, one new synonymy, and nine new records - Sanborn, Allen F. (Zootaxa, 2018)
The known cicada fauna of Panama is identified. Procollina quadrimaculata n. sp., P. stigmosa n. sp., Guyalna woldai n. sp., Herrera nigratorquata n. sp., H. sigillata n. sp. and Conibosa megalopercula n. sp. are described as new. Proarna germari Distant, 1905 n. syn. is shown to be a junior synonym of Proarna invaria (Walker, 1850). Pacarina championi (Distant, 1881) is returned to Proarna Stål, 1864 to become Proarna championi Distant, 1881 n. comb. again. The first records of Proarna invaria (Walker, 1850), Guyalna bogotana (Distant, 1892), Dorisiana cachla (Distant, 1899), Ollanta modesta (Distant, 1881), Pacarina schumanni Distant, 1905, Majeorona truncata Goding, 1925, Herrera lugubrina lugubrina (Stål, 1864), Calyria cuna (Walker, 1850), and Calyria telifera (Walker, 1858) are provided. The records for Ollanta modesta (Distant, 1881) are the first records of the genus Ollanta Distant, 1905 for Panama. The records for Calyria cuna (Walker, 1850), and Calyria telifera (Walker, 1858) are the first record of the genus Calyria Stål, 1862 and the Tribe Parnisini Distant, 1905 in Panama. Previous records of Dorisiana metcalfi Sanborn & Heath, 2014 (= Cicada viridis Olivier, 1790), Carineta fasciculata (Germar, 1830), and Selymbria stigmatica (Germar, 1834) are considered to be misidentifications of G. bogotana, C. maculosa (Torres, 1948), and S. pluvialis (Ramos & Wolda 1985) respectively so that D. metcalfi, C. fasciculata, and S. stigmatica are removed from the cicada fauna of Panama. The Panamanian record of Dorisiana semilata (Walker, 1850) is shown to be a mistake and the species is removed from the faunal list as well. The currently known Panamanian cicada fauna is comprised of 54 described species along with six species from the literature that remain undetermined from 22 genera, seven tribes and three subfamilies. Bergalna xanthospila (Germar, 1830) is reassigned to Dorisiana Metcalf, 1952 to become Dorisiana xanthospila (Germar, 1830) n. comb. Fidicinoides flavibasalis (Distant, 1905) is reassigned to Guyalna Boulard & Martinelli, 1996 to become Guyalna flavibasalis (Distant, 1905) n. comb.